2019
DOI: 10.5334/paah.43
|View full text |Cite
|
Sign up to set email alerts
|

Weighted Vest Training in Community-Dwelling Older Adults: A Randomized, Controlled Pilot Study

Abstract: Objectives:To determine if weighted vests dosed at 10% of body weight, when added to a home exercise program, provides stimulus sufficient to improve strength, sit to stand performance, and aerobic capacity in community-dwelling older adults. Methods: Nineteen participants (mean age = 68.7 +/-5.9 SD) were randomly assigned in a 1:1 fashion into either an exercise only control group or an exercise plus weighted vest at 10% of body weight intervention group. All participants performed the same home exercise prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The snatch process was divided into six phases in most previous studies; they are the first pull phase, the transition phase, the second pull phase, the turnover phase, the catch phase, and fully stand phase [ 11 , 21 24 ]. And they reported that the phases before the full stand were the most important in snatch [ 20 , 22 , 25 , 26 ]. In the present study, the snatch action from start to end of squat position, which is consistent with literature, was divided as the knee extension phase, the knee flexion phase, the force phase, the inertial ascent phase, the squat support phase, and the support completion phase, which were abbreviated as M 1- M 6 [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…The snatch process was divided into six phases in most previous studies; they are the first pull phase, the transition phase, the second pull phase, the turnover phase, the catch phase, and fully stand phase [ 11 , 21 24 ]. And they reported that the phases before the full stand were the most important in snatch [ 20 , 22 , 25 , 26 ]. In the present study, the snatch action from start to end of squat position, which is consistent with literature, was divided as the knee extension phase, the knee flexion phase, the force phase, the inertial ascent phase, the squat support phase, and the support completion phase, which were abbreviated as M 1- M 6 [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Klentrou et al (2007) had postmenopausal women complete multimodal exercise for 65 min per day, 3 days per week over 12 weeks, wearing a WV (progressively increased up to 15% of participants body weight), and found a significant reduction in serum osteocalcin levels (a bone resorption marker) and improved ankle plantar-flexion strength [11]. In addition, Mierzwicki (2019) revealed 12 weeks of lower extremity exercises with WV loading equivalent to 10% of participants bodyweight improved hip muscle strength, 30-sec chair rise,2-min step and 6-min walk test performance in older adults [12].…”
Section: Introductionmentioning
confidence: 99%